Urban public finance in developing countries - Bahl, Roy W.; Linn, Johannes F. (New York: Oxford University Press, 1992)
Designed for public finance and urban economists involved in Third World countries, this text discusses such subjects as urbanization and national planning, the urban fiscal problem in developing countries, property taxation, pricing urban services, and government expenditure.
Includes bibliographical references and Index
Keywords: Intergovernmental fiscal relations Developing countries; Developing countries; Intergovernmental fiscal relations